Water immersion and one-year storage influence the germination of the pyrenes of Copernicia alba Morong, a palm tree from a neotropical wetland - Soares, Vanessa Couto; Daibes, Luís Felipe [UNESP]; Damasceno-junior, Geraldo Alves; Lima, Liana Baptista De (Instituto de Pesquisas Ambientais, 2022)
Palm seeds are known for displaying dormancy and a thick endocarp that delays germination and embryo growth, but water treatments may accelerate their germination process. Additionally, ex-situ conservation of arecaceae species may cause loss of seed viability over time. Data on seed dormancy and storage have been neglected for many native palm species in Brazil. Therefore, we investigated the effect of water treatments and one-year storage on the germination of Copernicia alba Morong, a palm tree from the Brazilian Pantanal wetland. Fresh and stored pyrenes were immersed in water (at room temperature for 24, 48, and 72h) and in hot water (~75°C for 5 and 10-min). Fresh pyrenes germinated up to 84% in control, reaching 100% after water immersion for 48 and 72h. One-year storage reduced germination by almost 50%, but water immersion slightly increased the germination of stored pyrenes. Hot water decreased germination for both fresh and stored pyrenes. Seeds of C. alba may be classified as orthodox seed storage behavior. Taken all together, water treatments at room temperature improved the germination of the pyrenes. In contrast, long-term seed storage and hot-water treatments may jeopardize germination.

As sementes de palmeiras geralmente apresentam dormência e um endocarpo espesso que retarda a germinação e o crescimento do embrião, contudo, tratamentos com água podem acelerar o processo de germinação das suas sementes. Além disso, a conservação ex-situ de sementes pode causar perda de viabilidade das sementes de Arecacea especies ao longo do tempo. Dados sobre dormência e armazenamento de sementes têm sido negligenciados para muitas espécies de palmeiras nativas no Brasil. Por conta disso, nós investigamos o efeito da imersão em água e armazenamento de um ano sobre a germinação de sementes de Copernicia alba Morong, uma palmeira do Pantanal brasileiro. Pirênios recém-colhidos e armazenados foram imersos em água a temperatura ambiente por 24, 48 e 72h e água quente (~75°C por 5 e 10 min). Pirênios recém coletados germinaram 84% no controle, atingindo 100% após imersão em água por 48 e 72h. O armazenamento de um ano reduziu a germinação em ~50%, todavia, a imersão em água promoveu a germinação dos pirênios armazenadas. A água quente diminuiu a germinação dos pirênios frescos e os armazenados. De acordo com os resultados, sementes de C. alba podem ser classificadas em ortodoxas. Em geral, a imersão em água à temperatura ambiente aumentou a germinação dos pirênios. Entretanto, armazenamento for longa duração e tratamentos com água quente podem prejudicar a germinação.
A imersão em água e o armazenamento de um ano influenciam a germinação dos pirênios de Copernicia alba Morong, uma palmeira de um bioma alagado neotropical
Keywords: Arecaceae; caranday palm; hot-water treatment; Pantanal; seed storage; Arecaceae; armazenamento de sementes; carandá; Pantanal; tratamento com água quente